calcule:


a) (-n).(+6n) =


Resposta :

Resposta:

- 6n²

Explicação passo a passo:

( - n ) . ( + 6n )

= - n . 6n

= - n² . 6n

= - 6n²

Resposta:

resposta:        -6n²

Explicação passo a passo:

Simplificando expressão algébrica:

[tex](-n).(+6n) = [(-1).6].(n.n) = -6n^{2}[/tex]

Saiba mais sobre expressões algébricas, acessando:

https://brainly.com.br/tarefa/48622432

https://brainly.com.br/tarefa/47108206

https://brainly.com.br/tarefa/48364141

https://brainly.com.br/tarefa/47118936

https://brainly.com.br/tarefa/48332386